PROBLEMATIC OF MÖBIUS SYNDROME- CASE STUDY - Tabachová, Jana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article focuses on the problematic of Möbius syndrome, a specific description of a child with this syndrome. This is a very rare syndrome. At the time of diagnosing this girl‘s syndrome, doctors in the Czech Republic had almost no experience and had no seen any other child with Möbius syndrome. So she got the intensive care specific for this syndrome just before her third birthday. The aim of our study was to obtain data in motor development, cognitive skills and abilities and especially to obtain information about speech development. In this article, we try to capture the main therapeutic approaches that led to the development of communication skills and promote the development of all language levels.